Testing The Equality Of Location Parameters For Skewed Distribution Using S1 With High Breakdown Robust Scale Estimators. - Yahaya, S.S. Syed; Othman, Prof.Madya Abdul Rahman; Keselman, H. J. (2004)
A simulation study had been carried out to compare the Type I error and power of S1 , a statistic recommended by Babu et al {1999) for testing the equality of location parameters for skewed distributions.